The impact of cockroach control intervention on infectious diarrhea in Songjiang District, Shanghai, China - an interrupted time series analysis - Jie Feng; Chi Zhang; Bowen Pang; Meng Li; Xihong Lv; Ye Yao (Frontiers in Public Health)
IntroductionInfectious diarrhea, as one of the oldest infectious diseases, has been fought against by people for hundreds of years. From changing lifestyle habits to developing new drugs, people have been tirelessly searching for ways to reduce the burden of diarrhea. This study evaluated the impact of cockroach control intervention on infectious diarrhea from the perspective of public health and explored influencing factors, providing practical suggestions for implementation in various regions.Methods2,471 positive cases of diarrhea and 14,788 outpatient visits were included for analysis. Using the annual cockroach control intervention as the interruption time point, we observed the number of cases and visits for 12 months before and after, established interruption time series to evaluate the impact of cockroach control intervention on diarrhea in the population, and used hypothesis test to determine potential influencing factors.ResultsConducting an annual cockroach control intervention in Shanghai Songjiang District help reduce the number of diarrhea cases by 23.58% and the number of outpatient visits by 10.12% in the following year on average from 2020 to 2022. The temperature during the intervention in June 2022 showed a significant increase compared to 2020 and 2021; The effectiveness of cockroach control interventions was almost entirely reflected in Blattella germanica, while Periplaneta Americana were not affected.ConclusionUnder the combination of local natural conditions and comprehensive prevention measures, regular cockroach control interventions have a promising supporting effect on reducing the disease burden of diarrhea in the population and a certain effect on reducing the symptom burden. However, the intervention effect is affected by numerous factors such as temperature and cockroach species. If local baseline data can be consulted before intervention to select targeted intervention time and prevention methods, it is easier to achieve ideal results.